A prospective study on antibiotic prescribing pattern among in-patients of medicine department of a tertiary care hospital - S., Anulakshmi; Yadavalli, Annapurna (International Journal of Basic & Clinical Pharmacology, 2020)
Background: Irrational prescription is a major contributor to the antimicrobial resistance. Tertiary care centres in a state are the centres of excellence where policies are framed. So, they have an important role in promoting rational antibiotic prescription. Methods: The study was conducted on in-patients of medicine ward in government medical college, Calicut, for a period of 2 months (January to February 2018), The data was collected from IP case records of patients. The parameters checked includes appropriateness of the antibiotic as, to whether it is according to our hospital antibiotic policy, whether de-escalation and change to oral drug was done, whether it is prescribed by generic name, is it given as fixed drug combination (FDC), is it from national list of essential medicine. Results: Among the 135-prescription analyzed, total 225 antibiotics were used. Cephalosporins (32%) were the most commonly used. Of this only 40% was given by generic prescription. 27% was FDCs. 55% was from national list of essential medicines and 69% of them were ‘WATCH’ drug according to WHO Antibiotic Policy. Regarding appropriateness of prescriptions around 56% included right drug, 93% had right dose and frequency, and 70% had right duration and 100% were given through right route. Conclusions: Strict adherence to hospital antibiotic policy and plan for effective teaching programs regarding antibiotic resistance and importance of rational prescription of antibiotics can improve the quality of antibiotic prescription and minimize antibiotic resistance.